MiR‐211 and MITF modulation by Bcl‐2 protein in melanoma cells. Issue 12 (24th November 2015) - De Luca, Teresa; Pelosi, Andrea; Trisciuoglio, Daniela; D'Aguanno, Simona; Desideri, Marianna; Farini, Valentina; Di Martile, Marta; Bellei, Barbara; Tupone, Maria Grazia; Candiloro, Antonio; Regazzo, Giulia; Rizzo, Maria Giulia; et al.
Abstract : Melanoma, the most lethal form of skin cancer, is frequently associated with alterations in several genes, among which the Bcl‐2 oncogene plays an important role in progression, chemosensitivity and angiogenesis. Also microRNA (miRNA) are emerging as modulators of melanoma development and progression, and among them, miR‐211, located within the melastatin‐1/TRPM1 (transient receptor potential cation channel, subfamily M, member 1 protein) gene, is prevalently expressed in the melanocyte lineage and acts as oncosuppressor. Using several human melanoma cell lines and their Bcl‐2 stably overexpressing derivatives, we evaluated whether there was a correlation between expression of Bcl‐2 and miR‐211. Western blot analysis and quantitative real‐time polymerase chain reaction demonstrated reduced expression of pri‐miR‐211, miR‐211, TRPM1, and MLANA levels, after Bcl‐2 overexpression, associated with increased expression of well‐known miR‐211 target genes. Overexpression of mature miR‐211 in Bcl‐2 overexpressing cells rescued Bcl‐2 ability to increase cell migration. A decreased nuclear localization of microphthalmia‐associated transcription factor (MITF), a co‐regulator of both miR‐211 and TRPM1, and a reduced MITF recruitment at the TRPM1 and MLANA promoters were also evidenced in Bcl‐2 overexpressing cells by immunofluorescence and chromatin immunoprecipitation experiments, respectively. Reduction of Bcl‐2 expression by small interference RNA confirmed the ability of Bcl‐2 to modulate miR‐211 and TRPM1 expression. © 2015 Wiley Periodicals, Inc.